1978
DOI: 10.1103/physrevlett.41.354
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Structures in theppTotal-Cross-Section Difference of Pure Helicity States in the Mass Range of 2100 to 2500 MeV

Abstract: We have measured the difference between the pp total cross sections for parallel and antiparallel longitudinal spin states at beam momenta of 1.0, 1,1, 1.30, 1.58, 1.71, 2.1, and 2.25 GeV/c in a transmission counter experiment. These results reveal new structure in the p\^ range of 1.0 to 2.5 GeV/c.Previously we reported measurements of the difference between the pp total cross sections for parallel and antiparallel spin states, Aa^=a tot (r)-a tot «, using a longitudinally polarized beam and target at£ lab = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
11
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(16 citation statements)
references
References 20 publications
5
11
0
Order By: Relevance
“…The longitudinal spin-dependent proton-proton total cross-section difference ∆σ L measurements at the zero-gradient synchrotron (ZGS) [1] stimulated a high level of experimental and theoretical activity to search for dibaryons, mostly with isospin 1, through the 80's. Details of this period can be found in reviews [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal spin-dependent proton-proton total cross-section difference ∆σ L measurements at the zero-gradient synchrotron (ZGS) [1] stimulated a high level of experimental and theoretical activity to search for dibaryons, mostly with isospin 1, through the 80's. Details of this period can be found in reviews [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…1 The total-cross-section difference in pure longitudinal spin states for p-d interactions has been measured at momenta from 1.1 to 6 GeV/c. Spin-dependent Glauber-type corrections and other corrections have been made to obtain Aa L (pn) and Acr^^^O).…”
mentioning
confidence: 99%
“…The story began when Auer et al (12) at the Argonne National Laboratory (ANL) observed striking peaks in AO"L = O"(�)-O"(:::t ), the difference in total cross sections measured with longitudinally polarized beam and target with spins parallel or opposed. A similar peak has since been found in AO"T = O"(j !…”
Section: Dibaryonsmentioning
confidence: 99%